1995
DOI: 10.1177/096032719501400805
|View full text |Cite
|
Sign up to set email alerts
|

Fenoverine-induced rhabdomyolysis

Abstract: Fenoverine is a spasmolytic drug that inhibits calcium channel currents. We describe the clinicopathologic find ings in two patients with fenoverine-induced rhabdomyo lysis, of whom one died. A transient left-bundle-branch block was observed in both patients. In one case, pre-exist ing hepatic dysfunction may have induced accumulation of the drug. Concurrent treatment by fibrates, as observed in the second patient, may have been a predisposing factor for fenoverine-induced rhabdomyolysis. The incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Including our case, a total of 16 incidences of toxicologic LBBB were identified (Table ), with an average age of 44 (range 20‐86); 7 patients were female and 9 were male. The agents reported as the causative agent in LBBB were diverse, including psychiatric medications as in this case, antispasmodics (fenoverine), immunomodulators (rituximab), metals (colloidal gold and silver), analgesics (propoxyphene), cardiac glycosides (digoxin) and calcium channel blockers (verapamil, diltiazem and nifedipine) . Regarding the agents involved in our case, overdose of lamotrigine has been previously reported to cause LBBB; whereas there are no prior reports of LBBB in the setting of escitalopram overdose, there are two which have occurred in the setting of citalopram toxicity (citalopram is a racemic mixture of R‐citalopram and S‐citalopram).…”
Section: What Is New and Conclusionmentioning
confidence: 68%
See 2 more Smart Citations
“…Including our case, a total of 16 incidences of toxicologic LBBB were identified (Table ), with an average age of 44 (range 20‐86); 7 patients were female and 9 were male. The agents reported as the causative agent in LBBB were diverse, including psychiatric medications as in this case, antispasmodics (fenoverine), immunomodulators (rituximab), metals (colloidal gold and silver), analgesics (propoxyphene), cardiac glycosides (digoxin) and calcium channel blockers (verapamil, diltiazem and nifedipine) . Regarding the agents involved in our case, overdose of lamotrigine has been previously reported to cause LBBB; whereas there are no prior reports of LBBB in the setting of escitalopram overdose, there are two which have occurred in the setting of citalopram toxicity (citalopram is a racemic mixture of R‐citalopram and S‐citalopram).…”
Section: What Is New and Conclusionmentioning
confidence: 68%
“…one patient expired from sepsis and multiorgan dysfunction secondary to pneumonia 19 and the other due to liver failure in the setting of liver injury superimposed on pre-existing cirrhosis. 7 In conclusion, we summarize the literature regarding cardiotoxicity from drug overdose manifesting as QRS prolongation with a LBBB morphology. In these cases, patients were unlikely to respond to sodium bicarbonate therapy.…”
Section: What Is Ne W and Con Clus I Onmentioning
confidence: 99%
See 1 more Smart Citation
“…In Korea, it has been used since studies showed its clinical efficacy and safety for irritable bowel syndrome in 1989. However, in several cases it has been reported as a cause of rhabdomyolysis [15][16][17][18]. One report showed that 45 cases of rhabdomyolysis were attributed to this medication over the course of 5 years [19].…”
Section: Introductionmentioning
confidence: 99%
“…8 Plasma CK activity has been used in the evaluation of skeletal muscle disease, 12,14 muscle damage induced by exercise in humans 2 and in experimental models, 7,17 and drug-induced muscle toxicity in human and animal studies. 1,10,13 An increased plasma CK activity can be observed after parenteral drug injections. 15 Experience with analyses of serum enzymes such as alanine transaminase (ALT) has been successful in establishing consistent results in rats at our facility, as previously reported by others.…”
mentioning
confidence: 99%